Muhammadiyah-Based Community Engagement: Qur’anic Literacy, Worship Discipline, and Financial Empowerment: Keterlibatan Komunitas Berbasis Muhammadiyah: Literasi Al-Qur’an, Disiplin Ibadah, dan Pemberdayaan Keuangan - Daryanto Daryanto; Bayu Wijayantini; Taghfirul Azhima Yoga Siswa; Alfi Arif; Nursaid Nursaid; Taufik Sobri; Triawan Adi Cahyanto (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
This community service program aimed to strengthen Qur'anic literacy, worship discipline, and basic financial literacy among the congregation of Surau Wang Ulu, Kangar, Perlis, Malaysia, through a Muhammadiyah values-based empowerment approach. The ten-week program employed Participatory Action Research (PAR) across five stages: needs assessment, planning, implementation, evaluation, and follow-up. A total of 50 main participants took part, comprising 38 children aged 7–15 and 12 adults, with 25 parents and surau administrators serving as supporting participants. Interventions included talaqqi-based Qur'anic instruction, structured salah simulation, individual mentoring, parental engagement workshops, and basic financial literacy sessions. Data were collected through pre- and post-assessments, observation checklists, attendance records, and participant feedback, and analyzed descriptively. Post-programme assessments showed improvements across all measured indicators: tahsin recitation accuracy (72%), tajwid application (70%), beginner Qur'anic reading progression (65%), salah movement accuracy (68%), congregational prayer participation (75%), and basic financial literacy (60%). Community attendance throughout the programme reached 85%. These findings indicate that an integrated Muhammadiyah-based community service model combining spiritual, worship, and life-skills components can yield measurable improvements across religious and socioeconomic domains.